PTU-109 A pilot study of outreach testing for hepatitis C and linkage to care in a london centre for homeless persons. (22nd June 2015) - Selvapatt, N; Harrison, L; Brown, A
Abstract : Introduction: Outreach programmes provide high yield for case finding of Hepatitis C Virus (HCV), however linkage into care is consistently suboptimal. We pilot a pathway with outreach screening using oral swab testing followed by direct linkage into local hepatology clinic without need for a General Practitioner referral. Method: Hepatitis C screening at St Mungo's Centre for the Homeless, London was performed by a Specialist Hepatitis Nurse fortnightly between 28 th July 2014 and January 22 nd January 2015. A questionnaire assessed clients' understanding of HCV, previous testing and acceptability of screening and treatment. The OraQuick HCV Rapid Antibody Test (OraSure Technologies, Bethlehem, USA) was used. This oral swab testing kit provides a visual result within 20 min. All patients with positive results were counselled and had confirmatory blood tests, HCV viral load and genotype testing. These clients were then offered follow-up appointments at St Mary's Hospital Liver Unit or St Mungo's. Primary outcomes were incidence of HCV antibody positivity and the rate of linkage into care. Results: Thirty two clients completed the questionnaire: of which 22 (69%) reported that they had heard of HCV previously; 14 (44%) had been tested before; 29 (91%) would agree to screening. 29 (91%) reported oral swab testing was acceptable form of testing and 31 (97%) would consider treatment if offered. During the study period 95 clients underwent HCV testing. Overall 6 (6.3%) clients tested positive for hepatitis C antibody. On confirmatory testing 4 patients were identified with HCV mono-infection, 1 patient HIV co-infection, none with hepatitis B co-infection and 1 patient was HCV antibody positive on serological antibody testing but PCR negative on sequential testing suggestive of spontaneous clearance. All 5 viraemic patients attended follow-up within 14 days of diagnosis. 3 patients were Caucasian British, 1 Latvian and 1 Russian. To date one patient started treatment with pegylated interferon and ribavirin (genotype 3A) but developed virologic breakthrough at week 12 and therefore stopped. Another patient has been offered treatment but has elected to wait for interferon free therapies and three are currently being worked-up for treatment. Conclusion: Oral swab testing was an acceptable tool in this homeless person's outreach pilot study. Significantly higher rates of HCV were identified compared to the general population (<1%). In this pilot study, all patients were linked into appropriate care pathways which may be due to a combination of rapid, visual results and absence of intermediary referrals. Further work in larger populations over a longer period of time is needed to assess the health and cost effectiveness impacts of such measures. Disclosure of interest: N. Selvapatt Conflict with: Gilead, BMS, L. Harrison Grant/ Research Support from: Educational Grant from Janssen who supplied the OraQuick mouthswabs used in this pilot, A. Brown Speaker Bureau of: Abbvie, BMS, Gilead, Janssen, Merck.